Development of Methodology for Identification of Captopril in Medicines - Liliya, Logoyda (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The aim of the study was to development of a thin layer chromatography (TLC) method for the estimation of captopril. The pharmaceutical industry is under increased scrutiny to constrain costs and yet consistently deliver to market safe, efficacious products that fulfill medical needs. As a part of this, drug analysis also plays an important role in its contribution to new drug development. Materials and Methods: Standard analytical procedure for newer drugs or formation may not be available in pharmacopoeia and it is essential to develop new analytical methods which are accurate, precise, specific, linear, simple, and rapid. The analysis of captopril is described in pharmacopeia, but the aim of our researches was to improve to more rapid, simple, selective, more accurate, precise, reliable, less expensive methods by TLC of captopril in medicines and for using this methods for analysis of their metabolites in next step of researches. Results and Discussion: The method of identification of captopril in medicines by TLC has been developed. Established that the most optimal Rf observed using mobile phases: Chloroform R-propanol R (9:1). The detection limits of captopril in this system are 0.4 mcg. However, those mobile phases are the most express. We explored the validation characteristics - Specificity and suitability of the chromatographic system that met, the eligibility criteria established by the segmented polyurethane. Conclusion: We have been developed chromatographic methods of identification of captopril in medicines. The proposed methods are rapid, economical, simple, accurate, selective, precise, and applicable to the analysis of pharmaceutical dosage forms